2018
DOI: 10.1002/hrm.21941
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel examination of skills‐oriented human resource management and perceived skill utilization during recession: Implications for the well‐being of all workers

Abstract: This article examines whether organizations can enhance employee well‐being by adopting human resource management (HRM) practices strategically targeted to improve skill development and deployment in a recessionary context. Employee skill utilization is proposed as the mediating mechanism between HRM practice and well‐being. The role of workplace skill composition is also examined as a boundary condition within which HRM differentially impacts employee outcomes. Using a nationally representative survey of UK w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 106 publications
(165 reference statements)
0
46
0
Order By: Relevance
“…Higher education institutions are increasingly expected to engage with the challenges of the contemporary world. Policymakers have repeatedly asked for investment in personal skills as a route to building resilience and aiding recovery following the economic recession of 2008 (e.g., references [1,2]). The industry reinforces this call by requiring professionals who can fulfil the demands of the new contexts and trends, such as the Fourth Industrial Revolution [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education institutions are increasingly expected to engage with the challenges of the contemporary world. Policymakers have repeatedly asked for investment in personal skills as a route to building resilience and aiding recovery following the economic recession of 2008 (e.g., references [1,2]). The industry reinforces this call by requiring professionals who can fulfil the demands of the new contexts and trends, such as the Fourth Industrial Revolution [3].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the debate about automation and the future of work has brought this issue to the heart of the matter (e.g., OECD Employment Outlook, 2012 [1]). In industry, human resources departments are working towards identifying skills that can be more difficult to automate [2]. Employee skill utilization can be seen as a driver of employees' outcomes and the sustainability of 'best practice' arguments across all skill levels, even in the face of recession.…”
mentioning
confidence: 99%
“…Furthermore, given that career distress is a major cause of employee turnover (S. Hu, Creed, & Hood, 2017), our research will also inform how employee retention programs can be customized to retain employees who feel overqualified for their jobs. It is widely accepted that HRM systems should be customized and context‐specific to be effective (Latham & Piccolo, 2012; Okay‐Somerville & Scholarios, 2019). To this end, findings of this research are expected to provide insights as to how HRM systems can be customized to better accommodate the needs of a growing population of employees who feel overqualified for their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…What are relevant, though indirectly, may be those exploring the influences of the fit between HC and HRM on employee attitudes and behaviors, which may further affect organizational performance (see Table 3). While some studies did not find any statistically significant effect of the fit on employee wellbeing (Clinton & Guest, 2013;Okay-Somerville & Scholarios, 2019) or employment opportunities (van Harten et al, 2017), others revealed that the fit between HC and HRM can elicit positive employee attitudes and behaviors, such as increasing employees' satisfaction with their performance management (Decramer et al, 2013) and organizational citizenship behavior (OCB) , and lowering their turnover intentions (Schmidt, Pohler, et al, 2018).…”
Section: Empirical Validationsmentioning
confidence: 99%
“…Ferner & Almond, 2013;Lepak & Snell, 2002;Okay-Somerville & Scholarios, 2019) and public organizations(McKeown & Lindorff, 2011;Vyas & Zhu, 2017); and in both quantitative (e.g Clinton & Guest, 2013;Okay- Somerville & Scholarios, 2019;Urtasun & N uñez, 2012). and qualitative studies (e.g McKeown & Lindorff, 2011;.…”
mentioning
confidence: 99%